Advances in library administration and organization. Vol. 32 - Williams, Delmus Eugene; Golden, Janine (Emerald, 2014)
Volume 32 of Advances in library administration and organization bring together a collection of studies which highlight up and coming research that today's library managers and researchers face. The book will examine the challenges that library administrators encounter on a daily basis, review emerging trends and bring critical analysis to this area.
Includes index.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General.; Library & information sciences.; "Library, archive & information management".; Library & information services.; Library administration.; elektronické knihy; electronic books